IS RUSSIA’S GEOPOLITICAL REVENGE POSSIBLE IN THE SOUTH CAUCASUS: THE CASE OF GEORGIA (Вісник: Міжнародні відносини, 2025)
The “Rose Revolution” of 2003 in Georgia, the launch of the first Baku-Tbilisi-Ceyhan gas pipeline bypassing Russia in 2006, the Velvet Revolution of 2018 in Armenia, and finally the withdrawal of Russian “peacekeepers” from Nagorno-Karabakh in 2023 - these facts convincingly demonstrated the Kremlin’s loss of geopolitical primacy in the South Caucasus. For the first time in the last century and a half. Some experts were ready to cross Russia off the list of the most influential external actors in the South Caucasus region. However, the political events of October-December 2024 in Georgia showed that it was too early to write off the Russian Federation. Perhaps because the pro-Russian political project called “Georgian Dream”, having received sole power in Georgia as a result of the 2024 parliamentary elections, practically crossed out the reformist domestic policy of the third President of Georgia, M. Saakashvili, as well as questioned the commitment of the current Georgian authorities to the once proclaimed strategic course of Georgia towards Euro-Atlantic integration.Methods. The main methodological approaches to studying the influence of the Russian Federation on the formation and implementation of geopolitical priorities by the states of the South Caucasus were historical and geopolitical. In particular, the latter approach allowed us to trace the evolution of the foreign policy priorities of the ruling class of Georgia in the context of a changing world order.Results. The article examines the influence of the Russian Federation on domestic political processes and the development of Georgia’s foreign policy strategy after the collapse of the USSR in 1991. It is proven that the Russian military presence, as well as the Kremlin's targeted policy of inciting ethno-political conflicts in Abkhazia and the Tskhinvali region of Georgia, resulted in the Russian armed aggression against Georgia in August 2008. The author also notes the destructive role of the leaders of the leading EU countries, Germany and France, who, by refusing to provide Georgia and Ukraine with an Action Plan for NATO Membership in April 2008, actually contributed to the armed aggression of the Russian Federation against Georgia in August 2008. The EU's position on the issue of Georgia's territorial integrity in the post-conflict period was equally unconstructive. All this resulted not only in the de facto rejection of 20 percent of its internationally recognized state territory from Georgia, but also contributed to the loss of popularity, and later the power of the team of Georgian reformers led by M. Saakashvili. The Kremlin has benefited greatly from this, effectively bringing the pro-Russian political project “Georgian Dream” to power in sovereign Georgia. Having won a majority for the first time in the 2012 parliamentary elections, “Georgian Dream” has now built an authoritarian regime, the signs of which are repression of political opponents, oppression of freedom of speech, and selective justice. As a result, in June 2024, it was announced that Georgia's accession process to the EU was suspended. The biggest beneficiary of this decision was Russia, which showed that it still has enough leverage to keep Georgia and other countries of the South Caucasus in the orbit of its own geopolitical influence.Conclusions. The author’s analysis of the causes and consequences of the Russian Federation’s intervention in the domestic and foreign policy of sovereign Georgia showed that the main goal of the Kremlin’s policy is the desire to significantly limit the European integration aspirations of official Tbilisi. To achieve this goal, Moscow uses all the tools of imperial influence at its disposal, such as: bribery of the elites of the countries of the former USSR, economic pressure, information and psychological operations, armed aggression. This, in our opinion, temporary success of the Russian policy in Georgia is greatly facilitated by the Western policy of "pacification" of Russia, the victims of which are inevitably smaller in size and potential countries of the post-Soviet space, such as Georgia.Keywords: politics, geopolitical transformations, post-Soviet space, Russian Federation, Georgia, ethno-political conflicts, Euro-Atlantic integration
Keywords: politics; geopolitical transformations; post-Soviet space; Russian Federation; Georgia; ethno-political conflicts; Euro-Atlantic integration